Effectiveness of intraoperative use of dexmedetomidine in reducing the incidence of tachyarrhythmia after congenital cardiac surgery in neonates and infants: a doubly robust method estimation analysis. (2nd March 2023) - Bourgoin, Pierre; Jegard, Julien; Joram, Nicolas; Fox, Sylvain; Biard, Marc; Fernandez, Modesto; Baruteau, Alban Elouen; Dejoie, Thomas; Ferdynus, Cyril; Chenouard, Alexis
Abstract: OBJECTIVES: The antiarrhythmic effects of dexmedetomidine (DEX) have been suggested, but there are controversial reports on the effectiveness of intraoperative use of DEX to reduce the incidence of postoperative tachyarrhythmia (POT). METHODS: From a local European Congenital Heart Surgery Association database, we included patients operated for congenital heart diseases under cardiopulmonary bypass within a 5-year period (2017–2021), during which intraoperative use of high dose of DEX (1–1.4 µg/kg/h) was implemented. A doubly robust matching estimation of the causal effect of DEX on the incidence of POT was conducted. We combined a multimodal estimation model in patients not exposed to DEX (disease risk score) as well as a regression analysis in a matched cohort for patients exposured to DEX. RESULTS: From a cohort of 593 surgeries (514 patients) occurring during the study period, doubly matched analysis consisted of the analysis of 426 surgeries conducted under DEX or not (213 per group). The probability of developing POT in patients exposed to DEX was 6.6% (95% confidence interval 0.032–0.099) vs 14.5% (95% confidence interval 0.098–0.193) in the group of patients not exposed to DEX. The doubly robust matched estimation method showed a mean reduction of 8.8% (95% confidence interval −0.137 to −0.023) of POT when DEX is used for intraoperative anaesthesia. CONCLUSIONS: The use of high doses of DEX during anaesthesia for congenital heart surgery in neonates and infants is associated with a moderate but significant reduction of POT. Abstract : Tachyarrhythmias after congenital cardiac surgery, mostly consist of junctional ectopic tachycardia (JET).